Investigation TheWater Qualıty Of Çimenyenice Lake (Hafik- Sivas) - Mutlu, Ekrem; Kutlu, Banu; Demir, Tuğba (Journal of Selçuk University Natural and Applied Science, 2014)
Çimenyenice Lake is located in 9 km north of Hafik District of Sivas City, and its surface area is 0.57 km2. The altitude of this lake is 1,298 m, and it is fed with rain waters and snow waters, besides the water arising from deep of gypsum plateau. This natural lake is a very important habitat for aquatic birds in Sivas city, and it is under protection according to provisions of RAMSAR convention. The objective of this study is to determine the actual water quality characteristics of Çimenyenice Lake which is a natural lake. The study has started in November of 2011, and for 12 months, the samples have been taken monthly from 3 stations which have been chosen to reflect the properties of lake water homogenously. The parameters of temperature, pH, dissolved oxygen, salinity, and electrical conductance were measured via field type devices in region. Dissolved oxygen and temperature were measured via YSI brand 52 model oxygen meter, pH measurement was conducted with Orion brand 420A model pH-meter, the electrical conductance (μs/cm) and salinity (ppt) were measured by using YSI brand 30/50 FT model conductance-meter. Other water quality parameters of Suspended Solid Matters (SSM), chemical oxygen need (CON), total alkalinity, total hardness, total ammonium azote, nitrite, nitrate, phosphate, chloride, sodium, magnesium, calcium, and the heavy metals of ferrous, lead, copper and cadmium were analyzed in water samples taken to laboratory, and the analyses were executed within same day. As a result of performed study, the actual water quality of Çimenyenice Lake (Hafik-Sivas) was determined, it has been evaluated according to Surface Water Quality Management Regulation’s Inland Surface Water Classes criteria. A database was established for similar future to be executed in future.
Keywords: Water quality, Sivas, Çimenyenice Lake, Nutritive Element, Metal